(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The practice of kata, or pre-arranged, patterned movements in the martial arts, allows a student to learn specific basic movements, and to understand the meaning behind them. Many kata-based martial arts organize their curriculum into sets of practice. Using iaido (sword drawing) as an example, this paper demonstrates how a set of practice can build, one kata after the other, from simple to more complex ideas and provide a deeper understanding of the entire set.